Compliance with the smoke-free public places legislation in Nepal: A cross-sectional study from Biratnagar Metropolitan City - Basnet,LB; Budhathoki,SS; Adhikari,B; Thapa,J; Neupane,B; Moses,T; Dhimal,M; Pokharel,PK; Ghimire,A; Belbase,D; Khatri,S; Yadav,NK; et al. (PLoS One, 2022)
BackgroundSmoke-free legislation banning tobacco smoking in public places was implemented across Nepal in 2014 with the ambition to reduce the impact of second-hand smoking. As part of a comprehensive policy package on tobacco control, the implementation of the legislation has seen a marked reduction in tobacco consumption. Yet there remains uncertainty about the level of compliance with smoke-free public places.ObjectivesThis study assesses the compliance with smoke-free laws in public places and the factors associated with active smoking in public places in Biratnagar Metropolitan City, Nepal.MethodsA cross-sectional study was conducted in the Biratnagar metropolitan city in Province 1 of Nepal from July to December 2019. A total of 725 public places within the metropolitan city were surveyed using a structured survey tool. Active smoking was the primary outcome of the study which was defined as smoking by any person during the data collection time at the designated public place.ResultsThe overall compliance with smoke-free legislation was 56.4%. The highest compliance (75.0%) was observed in Government office buildings. The lowest compliance was observed in eateries, entertainment, and shopping venues (26.3%). There was a statistically significant association between active smoking and the presence of ‘no smoking’ notices appended at the entrance and the odds of active smoking in eateries, entertainment, hospitality, shopping venues, transportations and transits was higher compared to education and health care institutions. None of the ‘no smoking’ notices displayed fully adhered to the contents as prescribed by the law.ConclusionAs more than half of the public places complied with the requirements of the legislation, there was satisfactory overall compliance with the smoke-free public places law in this study. The public venues (eateries, shopping venues and transportations) that are more frequently visited and have a high turnover of the